Investigating the Incorporation of Digital Literacy and 21st-Century Skills into Postgraduate Students’ Learning Activities - Lailatul Maya; Muchlas Suseno (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Students in higher education institutions require digital literacy and 21st-century skills for their learning activities. Despite the reality of students born into digital technologies that have become increasingly integrated into learning activities, no studies have looked into the situation, particularly study in the context of postgraduate students. This study aims to determine the extent of Master of English Language Education (MELE) students’ incorporation of digital literacy and 21st-century skills within their learning activities. This study was carried out using a survey research method. The sample consisted of 34 MELE students from Jakarta State University enrolled in various gap years (2019-2021) in the Master English Language Education department. The data were collected using 24 questionnaire items. The instruments were employed based on the International Society for Technology in Education (ISTE) Student Standard and disseminated using Google Form. The findings revealed that most MELE students had a high level of digital literacy and 21st-century skills. However, some students marked themselves as having low levels on it. Thus, the researchers recommended that the students enhance their engagement with technology, incorporate 21st-century skills, and develop digital literacy according to today’s requirements for completing their learning goals.